HIV testing in the dental setting: perspectives and practices of experienced dental professionals. Issue 3 (4th March 2018) - Parish, Carrigan L.; Siegel, Karolynn; Liguori, Terri; Abel, Stephen N; Pollack, Harold A; Pereyra, Margaret R.; Metsch, Lisa R.
ABSTRACT: The dental setting is a largely untapped venue to identify patients with undiagnosed HIV infection. Yet, uptake of rapid HIV testing within the dental community remains low. This study sought to better understand the experiences of dental professionals who have administered the test and how these experiences might inform efforts to promote greater uptake of rapid HIV testing in dental settings. Qualitative interviews were conducted with United States dentists ( N  = 37) and hygienists ( N  = 5) who offered rapid HIV testing in their practices. The data revealed both the impeding and facilitating factors they experienced in implementing testing in their setting, as well as the reactions of their staff, colleagues, and patients. Overall, participants viewed rapid HIV testing favorably, regarding it as a valuable public health service that is simple to administer, generally well accepted by patients and staff, and easily integrated into clinical practice. Many had experience with a reactive test result. Participants described facilitating factors, such as supportive follow-up resources. However, they also cited persistent barriers that limit acceptance by their dental colleagues, including insufficient reimbursement and perceived incompatibility with scope of practice. The widespread adoption of routine HIV testing amongst dental professionals will likely require an expanded notion of the proper scope of their professional role in overall patient health, along with greater support from national dental organizations, dental education, and dental insurance companies, especially in the form of sufficient reimbursement.